2014
DOI: 10.1589/jpts.26.1965
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Physical Fitness Status between Middle-aged and Elderly Male Laborers According to Lifestyle Behaviors

Abstract: [Purpose] We sought to examine the relationship between lifestyle behavior and physical fitness in middle-aged and elderly laborers. [Subjects] In total, 2,469 male laborers between 45 and 64 years of age residing in eight cities in South Korea were studied between January and December 2007. [Methods] Age, height, and weight were evaluated as general characteristics. Lifestyle behavior items included exercise, dietary habits, smoking, drinking, and sleeping hours. Physical fitness was assessed by measuring mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…With regard to the presence of exercise habits, the scores for physical functions, exercise self-efficacy, and self-rated health of participants who had exercise habits were significantly better than those of participants who had no exercise habits. Previous studies found that good exercise habits were associated with good physical fitness 3 , 25 ) and good self-rated health 26 ) , which is congruent with the results of the present study. Self-efficacy is one of the principal Social Cognitive Theory constructs and is defined as an individual’s beliefs about his/her own ability to engage in a task successfully to obtain a desired outcome 27 ) .…”
Section: Discussionsupporting
confidence: 93%
“…With regard to the presence of exercise habits, the scores for physical functions, exercise self-efficacy, and self-rated health of participants who had exercise habits were significantly better than those of participants who had no exercise habits. Previous studies found that good exercise habits were associated with good physical fitness 3 , 25 ) and good self-rated health 26 ) , which is congruent with the results of the present study. Self-efficacy is one of the principal Social Cognitive Theory constructs and is defined as an individual’s beliefs about his/her own ability to engage in a task successfully to obtain a desired outcome 27 ) .…”
Section: Discussionsupporting
confidence: 93%
“…PA influences health improvement, improves the cardiorespiratory condition, body composition and also benefits psychosocial being. Besides, PA is an important segment in prevention and treatment of diabetes (Kelley & Kelley, 2013;Bae et al, 2015;Yong et al, 2014;Lee et al, 2015;Boström et al, 2012;Alberga et al, 2011). Previous studies researched VO2max changes after interventions with certain experimental treatment of aerobic characteristics at a given time span (Shim et al, 2010;Askarabadi et al, 2012;Rezaimanesh & Amiri-Farsani, 2011;Osei-Tutu & Campagna, 2005).…”
Section: The Effects Of Physical Activity On Vo2max Increasementioning
confidence: 99%
“…The Ministry of Education, Culture, Sports, Science, and Technology 1 ) recommended that preschool children engage in physical activity for at least 60 minutes daily. It is important to develop the habit of physical activity to improve one’s life expectancy right from preschool age 2 , 3 ) . Skeletal muscle mass is a principal factor of body movement, but there are few reports on skeletal muscle mass of preschool children.…”
Section: Introductionmentioning
confidence: 99%
“…The BMI formula 8 ) reported by Komiya used to calculate the body fat mass and body fat-free mass were derived from the following three methods: 1) the formula reported by Lohman 9 ) , which involves weight and the log-transformed sum of skinfold thickness; 2) formula according to Houtkooper et al 10 ) , which is based on body density and body resistance derived by SF-BIA; and 3) formula based on total body water, as determined by using deuterium oxide 11 ) and SF-BIA 6 ) . Komiya estimated the body fat mass index (FMI, fat mass/height 2 ) as the average of body fat mass values from these three methods, and the BMI formulas 8 ) were derived from regression analysis of the FMI based on BMI. The BMI formulas 8 ) are as follows: body fat mass (kg) = (0.408 BMI − 3.937) height 2 (m), for boys; body fat mass (kg) = (0.462 BMI − 4.432) height 2 (m), for girls.…”
Section: Introductionmentioning
confidence: 99%